Theoretical study of SO2 adsorption on goethite (1 1 0) surface - Zubieta, Carolina Edith (2014)
Adsorption of SO2 on fully hydrated and partially dehydrated (1 1 0) surface of goethite (α-FeOOH) has been investigated using density functional theory (DFT) and periodic conditions. Different degrees of dehydration were modeled by eliminating one or two water molecules from the fully hydrated surface. Calculations indicate that SO2 shows preference to adsorb on dehydrated surface and the transformation to surface sulfite, bisulfite and sulfate was observed. In particular, surface sulfite can be formed over a variety of different dehydrated surfaces as monodentate and bidentate complexes. Theoretical vibrational frequencies of all the species have also been computed. Taking into account all the structures, we found frequency values within the 650–1030 cm−1 region due to SOFe stretching, and between 1010 and 1190 cm−1 due to SO stretching. Furthermore, monodentate mononuclear and bidentate binuclear sulfite complexes present distinctive features at low frequencies (600–700 cm−1).